2015
DOI: 10.1111/cpr.12163
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles inhibit murine photoreceptor‐derived cell proliferation and migration via reducing TGF‐β and MMP‐9 expression in vitro

Abstract: Results of our study indicate that ZnO nanoparticles suppressed cell proliferation and migration, and reduced production of TGF-β and MMP-9 at both gene and protein levels. Our findings contribute to the understanding of the molecular mechanisms that reduced TGF-β and MMP-9 levels inhibit cell proliferation and migration under ZnO nanoparticle influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 52 publications
(59 reference statements)
3
10
0
1
Order By: Relevance
“…ZnONPs increased lactate dehydrogenase release in medium, aggravate ROS level within cells, collapse mitochondrial membrane potential, block delayed rectifier potassium current, and attenuate expressions of Na + /K + -ATPase at mRNA and protein levels and its activity (19,20). ZnONPs also showed adverse effects on murine photoreceptor cells, via reducing TGF-β and MMP-9 expression in vitro (21). Regarding selective toxicity of ZnONPs to SIRC cells, it seems that there are some different proteins or signals with roles in cytotoxic pathway in SIRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…ZnONPs increased lactate dehydrogenase release in medium, aggravate ROS level within cells, collapse mitochondrial membrane potential, block delayed rectifier potassium current, and attenuate expressions of Na + /K + -ATPase at mRNA and protein levels and its activity (19,20). ZnONPs also showed adverse effects on murine photoreceptor cells, via reducing TGF-β and MMP-9 expression in vitro (21). Regarding selective toxicity of ZnONPs to SIRC cells, it seems that there are some different proteins or signals with roles in cytotoxic pathway in SIRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in NPs concentration in cells contributes its attachment on cell surface followed by its uptake in cytoplasm resulting in cell death. ROS are produced in the cells in response to ZnO NPs exposure leading to free radical formation which reacts with the cell organelles to cause enzymatic changes, facilitates cellular content disorganization ultimately resulting in apoptosis [76,77]. 7b) and DU145 ( Figure 7f) cells compared to treatments and more when compared with negative controls (Figure 7a,e).…”
Section: Dapi Stainingmentioning
confidence: 99%
“…It is also reported that ZnO nanoparticles induce death in proliferating cells. All these properties are very important for an IOL. Thus, the main objective of the present study is to prepare hydrophobic polymer‐ZnO nanocomposite films and study the effect of added ZnO on film properties that are important in manufacture and function of IOLs.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc oxide (ZnO) nanoparticles are known to be selective killers of proliferating cells. [16][17][18][19] It was also shown that ZnO nanoparticles and UV radiation have synergistic inhibitory effect on human lens epithelial cells. 20,21 Thus, nanocomposites of ZnO with hydrophobic polymers offer excellent scope for preparation of IOLs that resist cellular adhesion, and the same has been investigated in the present study.…”
Section: Introductionmentioning
confidence: 99%